Implications of Ozempic: A Semaglutide with Peptide (GLP)-1 Receptor Agonists Misused for Cosmetic Weight Loss - Renee E Reardon (Undergraduate Research Journal for the Human Sciences, 2025)
Ozempic, classified as a GLP-1 receptor agonist, is a semaglutide primarily prescribed for managing type 2 diabetes. It operates by mimicking the hormone glucagon-like peptide-1 (GLP-1), thereby prompting insulin secretion and reducing glucagon levels. Administered via weekly injections, it aids in regulating blood sugar levels by enhancing insulin production from the pancreas. Originally designed to assist diabetics in controlling their blood sugar, it was later discovered to be effective in promoting weight loss as well. However, individuals using Ozempic for weight loss may face elevated risks of experiencing gastrointestinal issues. This conclusion stems from comprehensive research analyzing insurance claims spanning from 2006 to 2020, involving over 5,000 patients across the United States. The findings highlighted a range of health complications, including biliary disease, gastroparesis, pancreatitis, and bowel obstructions among those using Ozempic for weight loss. Notably, a 2023 Tebra Survey revealed a significant demand for Ozempic for weight loss, with 22% of Americans seeking prescriptions from their physicians and 15% having personally used it for weight management. Additionally, 47% of respondents reported knowing someone who had used Ozempic for similar purposes. These statistics underscore the imperative for healthcare providers to educate patients regarding appropriate medication use and associated risks. Moreover, the study underscores the necessity for further research initiatives and public awareness campaigns to address the hazards associated with the misuse of pharmaceuticals for off-label purposes for cosmetic usage.
Keywords: Ozempic; Semaglutide; GLP-1; Weight Loss; Receptor; Misused; Peptide; Weight; Diabetes